Prison efforts to protect escaped prisoners (study at prison class II B Kuantan Singingi, Riau Province) - Kasmanto Rinaldi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Prisons as a place for the implementation of guidance for residents have caused various kinds of problems. The escape or flight of correctional residents is a phenomenon that continues to occur in prisons. This study was conducted with the aim of knowing the efforts made by the Kuantan Bay Class IIB Prison in protecting the escape or flight of residents from prison. The method used in this study is a qualitative method with a descriptive approach. Qualitative methods are used by researchers to provide data images based on what is seen which is collected and in the form of notes or documents or interviews to related sources. The results revealed that the escape of prisoners was caused by many factors, namely the inability to maximize supervision by prisons due to overcrowded, and the strong desire of the residents. to meet with family. The conclusion in this study is that the efforts made by The Kuantan Bay Class IIB Prison in protecting the residents of the fostered escape or run away are by establishing good relations between prison officers and the fostered residents, providing punishment for residents who have escaped, holding coaching, training and useful activities for the fostered residents. In addition, in terms of facilities and building conditions, building and security improvements are also carried out to minimize residents from escaping or running away from prisons such as the addition of barbed wire so that fences are not easy to climb. The conclusion of this study is effort.